Overcoming severe calcified lower extremity artery in lower limb salvage operation by using the Fogarty catheter and vein graft. Issue 8 (11th October 2021) - Kim, Dong Yeon; Kim, Yesol; Moon, Suk‐Ho
Abstract: Background: With severe vascular calcifications, vascular clamp application and utilizing the vessel for free flap recipient vessel becomes impossible. These obstacles can be overcome with the Fogarty catheter and vein graft. Patients and methods: When unclampable artery was encountered intraoperatively, a vein graft was used to make a clampable recipient site for six diabetic foot patients (ages from 42 to 80). The end of the Fogarty catheter was inserted into the proximal end of the vein graft and the transected calcified vessel in sequence, and the balloon of the catheter was used as an intraluminal tourniquet. The remaining end of the vein graft was connected to the distal vessel with a vascular clamp. Results: Five short vein graft revascularization for segmental arterial occlusion, one long vein graft for recipient artery elongation was done (lengths from 2 to 13.8 cm). Three delayed, and two immediate anterolateral thigh flaps (sizes from 15 to 150 cm 2 ) were performed, and one patient received vein graft revascularization surgery only. Postoperative vascular sonography of all six patients showed well‐maintained patency. Minor flap marginal disruption occurred at two patients but healed with conservative care. Postoperative follow‐up was done for 1–18 months (average 7.17). Limb salvage was achieved for five patients and all five free flaps survived. However, for one patient, arterial restenosis at popliteal artery a month later lead to major amputation. Conclusion: Using a Fogarty catheter and a vein graft may obtain perfect hemostasis during micro‐anastomosis and achieve successful microvascular reconstruction in patients with severely calcified vessels.